2020
DOI: 10.3390/plants9101323
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Dynamics of Leaf Stoichiometry of Phragmites australis: A Case Study From Yangguan Wetland, Dunhuang, China

Abstract: Leaf stoichiometry can enhance our understanding of leaf elements’ (C, N and P) concentrations and their corresponding ratios in an ecosystem with seasonal environment changes. This study quantified the seasonal dynamics of leaf stoichiometry of P. australis from Yangguan wetland, Dunhuang, China as a case study example. The leaf C concentration (LC) of P. australis changed between seasons and was 392.26 (g×kg−1), 417.35 (g×kg−1) and 392.58 (g×kg−1) in spring, summer and autumn, respectively. Leaf N and P conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
(85 reference statements)
1
7
0
Order By: Relevance
“…In general, in an environment with lower soil water content, leaves need to maintain a greater [C] leaf and specific leaf weight, as they must reduce photosynthetic and growth rates in order to reduce water consumption and improve their defenses against an adverse environment (Poorter and Bongers, 2006). Most studies have found that soil water content is negatively correlated with [C] leaf (Hu et al, 2018;Liu et al, 2020). In the present study, among these above-mentioned dominant factors, only SWC indirectly affected [C] leaf of L. virgaurea through three paths, namely SOC: STN path, SOC-STP path, and SOC-pH path (Figure 4A).…”
Section: Mechanisms For the Dominant Factors Affecting [C] Leaf Across Elevationsmentioning
confidence: 99%
“…In general, in an environment with lower soil water content, leaves need to maintain a greater [C] leaf and specific leaf weight, as they must reduce photosynthetic and growth rates in order to reduce water consumption and improve their defenses against an adverse environment (Poorter and Bongers, 2006). Most studies have found that soil water content is negatively correlated with [C] leaf (Hu et al, 2018;Liu et al, 2020). In the present study, among these above-mentioned dominant factors, only SWC indirectly affected [C] leaf of L. virgaurea through three paths, namely SOC: STN path, SOC-STP path, and SOC-pH path (Figure 4A).…”
Section: Mechanisms For the Dominant Factors Affecting [C] Leaf Across Elevationsmentioning
confidence: 99%
“…Meanwhile, the plant re-absorbs nutrients from senescent tissues, causing the transfer of nutrients in senescent leaves [44]. The herbs of annual vegetation will store a large amount of nutrients for reproduction in a short growth period [45], so the N and P contents in herb tissues gradually increased with the growing season.…”
Section: Seasonal Variations Of the C N And P Contents And Ratios Omentioning
confidence: 99%
“…For instance, leaf N and P concentrations of woody species decreased over the growing seasons, whereas the C:N, C:P, and N:P ratios showed the opposite trend (Dong et al, 2021). Similarly, the leaf N and P concentrations of herbs were significantly higher in the early growth season than in other growing seasons (Wu et al, 2010;Liu et al, 2020;Xiong et al, 2020). In contrast, Huang et al (2019) showed that riparian plants exhibited lower leaf N and P concentrations and higher leaf C concentration and ratios of C:N, C:P, and N:P in spring than in autumn.…”
Section: Introductionmentioning
confidence: 99%